The Role of Teachers as Innovative Learning Facilitators to Enhance Interest in Learning the Qur'an at TK Daruttaqwa Gulung - Jumatriadi JUMATRIADI (Formad English Foundation NTB-Jakarta, 2024)
The aim of this research is to analyze and understand the role of teachers as innovative learning facilitators in enhancing the interest in learning the Qur'an at TK Daruttaqwa Gulung. The research method employed is qualitative research with a case study design. The study was conducted at TK Daruttaqwa Gulung in the village of Lekor, Janaperia sub-district, Central Lombok Regency, West Nusa Tenggara. Data collection techniques in this research include in-depth interviews, classroom observations, and documentation. The data analysis technique used is content analysis. The analyzed data include interviews with teachers and parents, as well as direct observations of students. The research results indicate that the role of teachers as innovative learning facilitators has a positive impact on increasing the interest in learning the Qur'an. Teachers are able to create engaging learning experiences, foster discussions and explorations, utilize technology, establish a positive environment, and integrate relevant religious values. These efforts effectively enhance children's interest in learning the Qur'an and connect it to their daily lives.